Family conflict, chaos, and negative life events predict cortisol activity in low‐income children. Issue 4 (16th April 2018) - Doom, Jenalee R.; Cook, Stephanie H.; Sturza, Julie; Kaciroti, Niko; Gearhardt, Ashley N.; Vazquez, Delia M.; Lumeng, Julie C.; Miller, Alison L.
Abstract: Childhood poverty is hypothesized to increase risk for mental and physical health problems at least in part through dysregulation of the hypothalamic‐pituitary‐adrenal axis. However, less is known about the specific psychosocial stressors associated with cortisol reactivity and regulation for children living in poverty. The current study investigates negative life events, household chaos, and family conflict in preschool and middle childhood as potential predictors of cortisol regulation in low‐income 7–10 year olds ( N = 242; M age = 7.9 years). Participants were assessed in preschool and participated in a follow‐up assessment in middle childhood, during which diurnal free cortisol and free cortisol reactivity to the Trier Social Stress Test for Children (TSST‐C) were assessed. Household chaos during preschool predicted a more blunted diurnal cortisol slope in middle childhood. Greater negative life events during preschool and greater concurrent family conflict were associated with increased free cortisol reactivity in middle childhood.